The compressive properties and strengthening mechanism of the middle-trabecular beetle elytron plate. (May 2020) - Chen, Jinxiang; Yu, Xindi; Xu, Mengye; Okabe, Yoji; Zhang, Xiaoming; Tuo, Wanyong
For the development of new types of lightweight sandwich structures, the compressive properties and strengthening mechanism of the middle-trabecular beetle elytron plate were investigated for various values of η (the ratio of the trabecular radius to the honeycomb wall length). The results are as follows: (1) When η = 0.1, the increases in the compressive strength and standard energy absorption capacity of the middle-trabecular beetle elytron plate compared with the honeycomb plate exceed those of the end-trabecular beetle elytron plate; with an increase to η = 0.15, the compressive strength remains nearly the same, the energy absorption capacity undergoes a significant further increase, and the trabeculae exhibit Φ-type failure. (2) The strengthening mechanism that gives rise to the compressive properties of the middle-trabecular beetle elytron plate is proposed as follows: the trabeculae are located at the center of the honeycomb walls, where the maximum deformations would otherwise occur; they constrain the deformation of the honeycomb walls; and the number of trabeculae in the middle-trabecular beetle elytron plate also exceeds that in the end-trabecular beetle elytron plate. (3) Middle-trabecular beetle elytron plates have the advantage of facile manufacturing, which will establish a basis for promoting the application of beetle elytron plates.